Mortality and Sudden Cardiac Death Risk Stratification Using the Noninvasive Combination of Wide QRS Duration and Late Gadolinium Enhancement in Idiopathic Dilated Cardiomyopathy. (April 2018) - Marume, Kyohei; Noguchi, Teruo; Tateishi, Emi; Morita, Yoshiaki; Kamakura, Tsukasa; Ishibashi, Kohei; Noda, Takashi; Miura, Hiroyuki; Nishimura, Kunihiro; Nakai, Michikazu; Yamada, Naoaki; Tsujita, Kenichi; et al.
Abstract : Background: The aim of this study was to investigate whether the combination of QRS duration ≥120 ms (wide QRS duration [wQRS]) and late gadolinium enhancement (LGE) is a precise prognostic indicator for dilated cardiomyopathy. Methods and Results: We investigated the association between the combination of LGE plus wQRS and the primary end point (all-cause death) and a composite of sudden cardiac death (SCD) or aborted SCD in 531 patients with dilated cardiomyopathy. We also analyzed the association between the combination of LGE and wQRS and these end points among patients with a class I indication for implantable cardioverter defibrillator implantation. We divided study patients into 3 groups according to LGE status and QRS duration: 2 negative indices (LGE negative and narrow QRS), 1 positive index (LGE positive or wQRS), or 2 positive indices (LGE positive and wQRS), and followed them for 3.8 years. Multivariable Cox regression analysis identified 2 positive indices as a significant predictor of all-cause death (hazard ratio, 4.29 [1.19–15.47]; P =0.026). Among 317 patients with a class I indication for implantable cardioverter defibrillator, the 5-year event rate of SCD or aborted SCD was the lowest in the 2 negative indices group (1.4%). With propensity score–matching cohorts, the 2 negative indices group had a significantly lower event rate of SCD or aborted SCD than the other 2 groups (hazard ratio, 0.12 [0.01–0.97]; P =0.046). Conclusions: The combination of LGE and wQRS provides additional prognostic stratification compared with LGE status alone and might improve the appropriate use of implantable cardioverter defibrillator therapy in patients with dilated cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.